2014
DOI: 10.1111/jfb.12489
|View full text |Cite
|
Sign up to set email alerts
|

Feeding habits and ontogenic changes in digestive enzyme patterns in five freshwater teleosts

Abstract: Feeding habits and the activity of digestive enzymes (total alkaline proteases, α-amylase and lipase) from dace Leuciscus leuciscus, roach Rutilus rutilus, Prussian carp Carassius auratus gibelio, perch Perca fluviatilis and pikeperch Sander lucioperca fry were studied in the Malye Chany Lake-Kargat Estuary (western Siberia, Russia). The diet of fry from all studied species was mainly composed of chironomid larvae and zooplanktonic organisms (i.e. cladocera and copepoda), whereas carnivorous species such as P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 72 publications
3
20
1
Order By: Relevance
“…In particular, A. nigrofasciatus was fed only with cladocerans and Artemia metanauplii, whereas the peak in α-amylase activity in P. splendida and C. urophthalmus was detected after their weaning onto an inert compound diet (López-Ramírez et al 2011;Uscanga-Martínez et al 2011;Toledo-Solís et al 2015). In addition, the α-amylase activity was higher in A. nigrofasciatus and C. urophthalmus than in P. splendida, confirming results from previous studies that reported a higher α-amylase activity in herbivorous, omnivorous, and detritivorous species in comparison with carnivorous ones (Falcón-Hidalgo et al 2011;Solovyev et al 2014).…”
Section: Trial 1: Changes In Digestive Enzyme Activities During Earlysupporting
confidence: 87%
“…In particular, A. nigrofasciatus was fed only with cladocerans and Artemia metanauplii, whereas the peak in α-amylase activity in P. splendida and C. urophthalmus was detected after their weaning onto an inert compound diet (López-Ramírez et al 2011;Uscanga-Martínez et al 2011;Toledo-Solís et al 2015). In addition, the α-amylase activity was higher in A. nigrofasciatus and C. urophthalmus than in P. splendida, confirming results from previous studies that reported a higher α-amylase activity in herbivorous, omnivorous, and detritivorous species in comparison with carnivorous ones (Falcón-Hidalgo et al 2011;Solovyev et al 2014).…”
Section: Trial 1: Changes In Digestive Enzyme Activities During Earlysupporting
confidence: 87%
“…Identification of the prey organisms and determination of the importance of each prey in the fish dietary regime was previously described in Solovyev et al (2014). The degree of similarity of diet between fish with different feeding habits was analysed by Morista index which was carried out using PAST, ver.…”
Section: Identification Of Fish Feeding Habits According To Primary Dietmentioning
confidence: 99%
“…The last but not the least, digestive enzyme activities in fishes are indicative of their feeding ecology and trophic niche in natural conditions, thus, correlating well with their diet (Solovyev et al, 2014). Generally, herbivorous, omnivorous and detritivorous fishes may have higher carbohydrase activity (i.e.…”
Section: The Relevance Of Assessing the Activity Of Digestive Enzymesmentioning
confidence: 99%